Bandit's Blood - Hawkins, Clint (New York Harper Paperbacks, 1993)
In a squalid cell awaiting a trial that is certain to end in his execution, gunslinger Wade Calhoun enters into a battle of lead and steel in the corrupt town of Tubac.
Keywords: Calhoun, Wade (Fictitious character)